A case study on the archival and information preservation practices of indigenous cultural heritage and knowledge systems in UP Baguio's Museo Kordilyera - De Vera, Joemer John C.
This research is a case study of the archival, curatorial, and preservation practices of UP Baguio's Museo Kordilyera. The Museo Kordilyera is a museum focused on the preservation and highlighting of Indigenous Knowledge Systems throughout the Cordillera Administrative Region. Through the usage of documentation provided by Museo Kordilyera and an interview with the Museum Director, this research established and recorded the preservation equipment, platform, and curatorial mechanisms by which Museo Kordilyera preserves Indigenous Knowledge Systems. This research posits and analyzes Museo Kordilyera's Co-curation model, publications, workshops, digitization, and Corditex intitiative as an example of a Community Archive.